2014
DOI: 10.1590/s1679-45082014rw2561
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral drugs and acute pancreatitis in HIV/AIDS patients: is there any association? A literature review

Abstract: In HIV-seropositive individuals, the incidence of acute pancreatitis may achieve 40% per year, higher than the 2% found in the general population. Since 1996, when combined antiretroviral therapy, known as HAART (highly active antiretroviral therapy), was introduced, a broad spectrum of harmful factors to the pancreas, such as opportunistic infections and drugs used for chemoprophylaxis, dropped considerably. Nucleotide analogues and metabolic abnormalities, hepatic steatosis and lactic acidosis have emerged a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 38 publications
0
33
0
1
Order By: Relevance
“…For many years, it has been known that HIV/AIDS is associated with the development of acute pancreatitis in *40-45% of patients [4,53,70]. Studies have also shown a correlation between drug-induced pancreatic toxicity and certain antiretroviral drugs [71].…”
Section: Hiv/aidsmentioning
confidence: 99%
“…For many years, it has been known that HIV/AIDS is associated with the development of acute pancreatitis in *40-45% of patients [4,53,70]. Studies have also shown a correlation between drug-induced pancreatic toxicity and certain antiretroviral drugs [71].…”
Section: Hiv/aidsmentioning
confidence: 99%
“…Many of the drugs prescribed in pharmacies routinely are suspected of causing AP. In addition, they pose a high risk with cumulative doses (Giorda et al 2014;Oliveira et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research efforts demonstrate a major role of oxidative stress risk in the development, and progression of most pancreatic diseases, including recurrent acute and chronic pancreatitis (Robles et al 2013). Drugs have been shown to increase the risk of developing AP (Stobaugh and Deepak 2014;Giorda et al 2014;Oliveira et al 2014). And the supplementation of certain medicinal herbal extracts with drug may reduce the stress caused by drugs (Lata et al 2014).…”
Section: Introductionmentioning
confidence: 99%